A Review on Literature of Islamic Economic Indonesia: Form 2014-2024: Lesson for Practitioners and Future Directions - Arsilan Nafi Hidayat; Muhamad Subhi Apriantoro (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This review aims to synthesize existing literature on Islamic economics in Indonesia from 2014 to 2024 by highlighting key findings, research trends, and practical implications for practitioners. It captures the dynamic development of Islamic economic thought and practice in Indonesia, particularly in areas such as Islamic finance, micro-business development, and economic policies grounded in Islamic values. Methodology: This study adopts a systematic literature review approach to collect and analyze relevant publications on Islamic economics in Indonesia during the 2014-2024 period. Relevant articles, reports, and academic documents were identified through comprehensive searches of academic databases and reputable journals using predefined inclusion criteria to ensure quality and relevance. A qualitative thematic analysis was then applied to code and categorize the literature into key themes, including Islamic finance, micro-business development, and Islamic-based economic policies, in order to identify recurring patterns, trends, and research directions. Results: The review reveals significant growth and diversification in Islamic economics research in Indonesia over the past decade. The literature shows a strong emphasis on the development of Islamic finance institutions, the role of Islamic microfinance in supporting small and micro enterprises, and the increasing integration of Islamic values into national and regional economic policies. The findings also indicate a growing alignment between academic research and practical implementation in the Islamic economic sector. Applications/Originality/Value: This review provides a comprehensive and structured overview of Islamic economics research in Indonesia, offering valuable insights for policymakers, practitioners, and scholars. Its originality lies in systematically mapping a decade of literature to identify dominant themes, practical lessons, and research gaps. The study serves as a reference for future research and supports evidence-based decision-making in the development and implementation of Islamic economic practices in Indonesia.